2011
DOI: 10.1111/j.1600-0714.2011.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stressful life events on the onset and duration of recurrent aphthous stomatitis

Abstract: Background Recurrent Aphthous Stomatitis (RAS) is a common and painful oral mucosal disease. Possible etiologies include genetics, vitamin deficiencies, trauma, immune dysfunction and stress. The goal of the present study was to examine the relationship between the occurrence, type, and magnitude of stressful events and the onset and duration of RAS episodes. Methods 160 subjects with a history of RAS completed a weekly phone survey for up to one year, providing data on the occurrence of RAS episodes and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 17 publications
4
65
0
8
Order By: Relevance
“…The mechanism of stress in this issue is not clear. However, it probably has its effects via multiple system changes like the production and activity of lymphocytes, and the production of cytokines and antibodies (12). Another possible mechanism is its ability to induce the para-functional habits, like biting the lips of the cheek and its forming predisposition due to trauma (1).…”
Section: Recurrent Aphthous Stomatitismentioning
confidence: 99%
“…The mechanism of stress in this issue is not clear. However, it probably has its effects via multiple system changes like the production and activity of lymphocytes, and the production of cytokines and antibodies (12). Another possible mechanism is its ability to induce the para-functional habits, like biting the lips of the cheek and its forming predisposition due to trauma (1).…”
Section: Recurrent Aphthous Stomatitismentioning
confidence: 99%
“…(33,34). In some studies, a direct relationship has been reported between stress and the occurrence of aphthous stomatitis (8,9,(33)(34)(35)(36)(37). Such a relationship could not be found in some other studies (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Essas úlceras apresentam-se de forma dolorosa, levando a um impacto negativo na qualidade de vida dos pacientes 11 , podendo restringir a ingestão de alguns alimentos e também comprometer uma adequada higiene oral, possibilitando um maior acúmulo de biofilme oral, o que aumenta o risco para o desenvolvimento de outros agravos bucais, como a doença periodontal e a cárie dentária 12 . Dessa forma, a EAR representa um problema que requer atenção, devido à sua alta prevalência e associação com dor e influência na qualidade de vida dos indivíduos afetados 13 . Como tratamento, são indicados variados agentes terapêuticos, dentre eles, medicamentos sistê-micos e agentes tópicos têm sido utilizados na redução dos sintomas e na busca de uma acelerada regeneração dessa lesão 14,15 , tais como a utilização de produtos naturais 16 , antibióticos 5 , anti-inflamatórios 17 , vitaminas 18 ou laser 19 .…”
Section: Objetivo: Realizar Uma Revisão Integrativa De Publicações CIunclassified